Queer lives across the wall : desire and danger in divided Berlin, 1945-1970 - Rottmann, Andrea (German and European studies, 2023)
"Queer Lives across the Wall examines the everyday lives of queer Berliners between 1945 and 1970, tracing private and public queer life from the end of the Nazi regime through the gay and lesbian liberation movements of the 1970s. Andrea Rottmann explores how certain spaces--including homes, bars, streets, parks, and prisons--facilitated and restricted queer lives in the overwhelmingly conservative climate that characterized both German postwar states. By examining both public and private urban spaces, the book draws a complex picture of how queer lives were lived, going beyond previous histories that focus on state surveillance and the persecution of male homosexuality. With a theoretical toolkit informed by feminist, queer, and spatial theories, the book combines previously unknown sources from the archives of the feminist and LGBTIQ* movements in police, Stasi, and prisoner files. As an intersectional history of lesbian, trans, and gay male lives in East and West Berlin, Queer Lives across the Wall illuminates the entanglements of gender, sexuality, and class."--